Employee Engagement: The Challenge for Diverse Human Resource Management of Private Hospitals in Thailand / ความผูกพันของพนักงานต่อองค์กร:ความท้าทายของการบริหารทรัพยากรมนุษย์ที่มีความหลากหลายของโรงพยาบาลเอกชนในประเทศไทย - นวัสนันท์ วงศ์ประสิทธิ์, Nawasanan Wongprasit / (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 1 (2558): January - April 2015, 2015)
ความผูกพันของพนักงานต่อองค์กร เป็นความรู้สึกเชิงบวกอย่างแรงกล้าของพนักงานที่มีต่อองค์กร อันเกี่ยวเนื่องมาจากบทบาท การทำงานในองค์กรจนถึงผลการปฏิบัติงานเพื่อบรรลุเป้าหมายองค์กร จนทำให้พนักงานแสดงออกด้วยความสมัครใจของการเป็นตัวแทน ที่ดีขององค์กร และอยู่ทำงานกับองค์กรเป็นระยะเวลานาน ความผูกพันของพนักงานต่อองค์กร มีผลต่อผลการปฏิบัติงานของพนักงานและความพึงพอใจของลูกค้า หากพนักงานที่มีความผูกพันต่อองค์กรสูง พนักงานจะอยากมาทำงาน ตั้งใจและทุ่มเททำงานหนักเพื่อบรรลุ ผลสำเร็จ ส่งผลให้ลูกค้าเกิดความพึงพอใจในบริการและองค์กรมีผลกำไรในที่สุด แต่ในทางตรงกันข้าม หากองค์กรใดพนักงานมีความผูกพันต่อองค์กรต่ำ พนักงานมักจะขาดงานบ่อย ไม่ตั้งใจทำงานเต็มที่ และมีอัตราการลาออกสูง ส่งผลให้การบริการไม่ราบรื่น ลูกค้าขาดความเชื่อมั่น อาจไม่มาใช้บริการ และองค์กรจะขาดทุนและปิดกิจการในที่สุด ผู้บริหารโรงพยาบาลเอกชนต่างตระหนักถึงความสำคัญดังกล่าวและได้พยายามหาแนวทางสร้างความผูกพันของพนักงานต่อองค์กรให้เกิดขึ้น หลักการบริหารทรัพยากรมนุษย์หนึ่ง คือ ความเข้าใจธรรมชาติและความต้องการของพนักงาน แล้วบริหารให้ตรงกับความต้องการนั้น ซึ่งพนักงานของโรงพยาบาลเอกชน ประกอบด้วย บุคลากรที่มีความหลากหลาย ทั้งในด้านหน้าที่ความรับผิดชอบ พื้นฐานการศึกษา ช่วงอายุ และเพศ ซึ่งผู้เขียนได้แบ่งออกเป็น 5 กลุ่มใหญ่ๆ อันประกอบด้วย 1) กลุ่มแพทย์ 2) กลุ่มพนักงานวิชาชีพที่ไม่ใช่แพทย์ เช่น เภสัชกร พยาบาล นักเทคนิคการแพทย์ นักรังสีเทคนิค และ นักกายภาพบำบัด 3) กลุ่มพนักงานวัยหนุ่มสาว 4) กลุ่มพนักงานที่มีอายุ 50 ปีขึ้นไป และ 5) กลุ่มพนักงานหญิง โดยสรุป จึงเป็นความท้าทายอย่างยิ่งของผู้บริหารโรงพยาบาลเอกชน ในการที่จะบริหารทรัพยากรมนุษย์ให้ประสบความสำเร็จท่ามกลางความหลากหลายดังกล่าว บทความนี้จึงขอนำเสนอ แนวทางการบริหารทรัพยากรมนุษย์ในโรงพยาบาลเอกชน ที่มีความหลากหลายและแตกต่างทางวิชาชีพเพื่อให้องค์กรโรงพยาบาลเอกชนในประเทศไทย ประสบความสำเร็จในการสร้างให้พนักงานมีความผูกพันต่อองค์กรสูงต่อไป   คำสำคัญ : ความผูกพันของพนักงานต่อองค์กร  ความหลากหลาย  การบริหารทรัพยากรมนุษย์  โรงพยาบาลเอกชน  ประเทศไทย   Employee engagement is a positive emotional commitment to the organization. It has evolved from research on the role of work in order to achieve performance. The employee’s engagement is demonstrated by his or her willingness to be an effective organization representative. Also, these employees usually remain in the organization for a long time. Employee engagement is related to the employee’s on-the-job performance and to customer satisfaction. Employee engagement may predict the employees’ willingness to do their work and their intention to work hard. The impact of high employee engagement is customer satisfaction and it contributes to making the organization profitable. On the other hand, the employee will be absent and low motivation for work if he or she has low engagement in the organization. It may lead to a high turnover rate in the organization and the customers will  become dissatisfied and will not have confidence in the services they receive, until finally it may lead to the organization’s losing money and going out of business. Private hospital administrators are aware of this phenomenon and attempt to find the guidelines for building high employee engagement in their organization. One principle of human resource management focuses on the nature and needs of employee management. Human resources in private hospitals are diverse. They are different in terms of responsibility, education, age, and gender. In this article, the employees were separated into five groups: 1) medical doctors; 2) medical professionals who were not medical doctors, such as pharmacists, nurses, medical technologists, X-Ray technicians and physical therapists; 3) younger generation employees; 4) 50 year old and older employees; and 5) female employees. In conclusion, it is a serious challenge for private hospital administrators to achieve successful human resource management policies with such a diverse range of employees. Their task is to decide how they can meet their employees’ needs and manage them. This article’s aim is to propose the guidelines for human resource management policies among five diverse groups of employees in order to achieve high employee engagement in private hospitals in Thailand. Keywords: Employee Engagement, Diversity, Human Resource Management, Private Hospital, Thailand
Keywords: ความผูกพันของพนักงานต่อองค์กร ความหลากหลาย การบริหารทรัพยากรมนุษย์ โรงพยาบาลเอกชน ประเทศไทย Employee Engagement, Diversity, Human Resource Management, Private Hospital, Thailand